Customer Engagement Behavior in the context of Continuous Service Relationships - Helle Haurum (Copenhagen Business School (CBS), 2018)
This thesis discusses customers' engagement behaviors (CEB) in the context of continuous service relationships (telecommunication provider and financial services' provider). CEB manifestations are agreed in literature and in business to be a potential source of value for the firm and valuable contributions have been made, mainly focusing at antecedents for CEB, the various CEB behaviors and consequences of CEB. Extant literature adopts mainly a firm-centric perspective and tends to be conceptual. This research adopts a customer-centric perspective. The methodology is qualitative and is performed via semi-structured in-depth interviews with individuals resulting in 40 touchpoint histories about their service relationships with their telecommunication provider and financial services provider. Furthermore, are qualitative data collected at the telecommunication firm, in terms of interviews with employees and participant observations at touch-points. CEB are definitely found to be potential sources for value-creation for the firm. CEB can however at times destroy value or cause lost CEB value (when CEB initiatives by the firm are not returned). From the perspective of customers are CEB manifestations part of their everyday Life. Customers manifest CEB to obtain a certain goal, sometimes targeted the firm, and sometimes targeted a group external to the firm. Customers manifest CEB by adopting a certain interaction style to facilitate goal achievement, and the way customers manifest CEB are sometimes inconsistent and follows not necessarily pre-figured sequences. Customers' CEB manifestations co-exist with the experiences customers have in their service relationships. CEB is sometimes manifested by customers to re-experience, reinforce or challenge what the customer is currently / has been experiencing. CEB is as well sometimes embedded in the service relationship to a degree, where customers' experiences and CEB become deeply intertwined or even become one and same construct, and sometimes is a CEB manifestation a consequence of a certain customer experience. CEB has changed the service relationship, and some of the recognized cornerstones in what constitutes a service relationship are challenged. This thesis suggests that CEB manifestations turn the service relationship into a plethora of (service) events of sometimes conflicting valence, which might disrupt the value creation process intended by the firm. This might be the reality of `the new service relationship'. These obvious managerial challenges are best solved by the firm, when the firm adopts a customer-centric approach and understands which situation(s) their customers are most frequently in (revolving around the firm). The firm should investigate which touch-points are relevant contingent the customer situation and finally how the touch-points could be best possible organized to stimulate for favorable CEB. This novel managerial concept is labeled `customer arenas'.
hdl:10398/9583
Keywords: 650